2011
DOI: 10.1063/1.3571285
|View full text |Cite|
|
Sign up to set email alerts
|

Guided Bloch surface wave polaritons

Abstract: The authors report on a theoretical investigation of guided polariton states arising from the strong coupling between quantum-well excitons and a Bloch surface wave confined at the interface between a uniform dielectric medium and a Bragg mirror. It is shown that the exciton–photon coupling is almost doubled as compared to a similar structure made in a conventional planar microcavity. It is also shown that, by simple engineering of the sample surface with silicon oxide deposition, one can efficiently produce o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 27 publications
2
47
0
Order By: Relevance
“…Recently, it has been suggested that similar phenomena could also be observed at the interface between a single Bragg mirror (DBR) and a homogeneous medium by exploiting strong light-matter coupling to Bloch surface waves. [10,11] Such Bloch surface wave polaritons (BSWP), [12] i.e. mixed excitations bound to the surface of the Bragg mirror,-which exploit the confinement of the optical mode due to total internal reflection as weel as a photonic bandgap-could be exploited for prospective polariton devices with high efficiency and controlled long range propagation, or for applications requiring high surface sensitivity such as optical sensors, [13,14] with clear advantages over alternative structures where metal deposition is required.…”
mentioning
confidence: 99%
“…Recently, it has been suggested that similar phenomena could also be observed at the interface between a single Bragg mirror (DBR) and a homogeneous medium by exploiting strong light-matter coupling to Bloch surface waves. [10,11] Such Bloch surface wave polaritons (BSWP), [12] i.e. mixed excitations bound to the surface of the Bragg mirror,-which exploit the confinement of the optical mode due to total internal reflection as weel as a photonic bandgap-could be exploited for prospective polariton devices with high efficiency and controlled long range propagation, or for applications requiring high surface sensitivity such as optical sensors, [13,14] with clear advantages over alternative structures where metal deposition is required.…”
mentioning
confidence: 99%
“…To date, several configurations supporting propagating modes confined in two dimensions have been suggested or demon-strated: optical fibers [3], ridge waveguides [4], PhC fibers [5], PhC waveguides [6], truncated PhC slabs [7], PhC wires [8], and PhC ridges [9,10]. Some of these configurations are shown in Fig.…”
Section: Introductionmentioning
confidence: 97%
“…In these structures, guided modes are characterized by asymmetric light confinement, which relies on a PBG only from the multilayer side and on TIR in all the other directions. These systems are not only appealing as platforms for optical sensors, but also for the study of the lightmatter interaction at the fundamental level, such as in the strong-coupling regime of quantum-well excitons [10]. One of the most interesting features of PhC ridges is that a guided mode can result even with ridges as thin as a few tens of nanometers [9].…”
Section: Introductionmentioning
confidence: 99%
“…A first theoretical proposal in 2011 [40], predicted the generation of BSWP using GaAs quantum wells deposited on top of a DBR. The first experimental demonstration of the formation of a BSWP was simultaneously obtained in 2014 from two different research teams [38,41].…”
Section: Bloch Surface Wave Polaritonsmentioning
confidence: 99%